Government Policy in Improving Human Resource Competencies Based on Digital Technology - Rojak, Jeje Abdul (Bulletin of Science, Technology and Society, 2024)
This study analyzes the effectiveness of government policies to improve digital technology-based human resource competencies in Indonesia and identifies barriers to their implementation. Based on a literature review and normative juridical analysis, it was found that while policies such as Presidential Regulation Number 95 Year 2018 have provided a relevant framework, their implementation is still impeded by a lack of innovation in training design, the digital divide in remote areas, and weak coordination between stakeholders. Lack of supportive regulations and low digital literacy among teachers and government employees are also significant obstacles. This research recommends the reinforcement of regulations, improvement of infrastructure, innovation of training programs, and development of a monitoring and evaluation system to support the success of the policy. This study contributes to the strategic evaluation of digital competency policies as a foundational step toward workforce readiness in the industrial era 4.0.